The use of tobacco, alcohol and other drugs by young Aboriginal people in Albany, Western Australia - Gray, Dennis; Morfitt, B.; Ryan, K.; Williams, S. (1997)
This paper describes patterns of tobacco, alcohol and other drug use among Aboriginal people aged 8 to 17 years in the town of Albany, Western Australia. Of a total of 110 young Aboriginal people residing in the town in the town at the time of the study, 105 were interviewed by two trained Aboriginal research assistants using interview schedules that included questions based on the national guidelines for the comparability of studies of drug use among young people.The most commonly used drugs were tobacco, alcohol and cannabis. Use of other substances was usually experimental. The majority (57 per cent) of this population had not used any drugs, 13 per cent made some use of alchol/or tobacco, 15 per cent were polydrug users, and 15 per cent were frequent polydrug users. Use of drugs increased with age: 48 per cent of those aged 15 to 17 were frequent polydrug users. Tobacco consumption was greater and alcohol use less than that reported among Western Australian secondary school children of comparable age.